2021
DOI: 10.3310/hsdr09140
|View full text |Cite
|
Sign up to set email alerts
|

Family and health-care professionals managing medicines for patients with serious and terminal illness at home: a qualitative study

Abstract: Background More effective ways of managing symptoms of chronic and terminal illness enable patients to be cared for, and to die, at home. This requires patients and family caregivers to manage complex medicines regimens, including powerful painkillers that can have serious side effects. Little is known about how patients and family caregivers manage the physical and emotional work of managing medicines in the home or the support that they receive from health-care professionals and services. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 156 publications
2
46
0
Order By: Relevance
“…The considerable effort and burden of responsibility for medications, especially controlled drugs, has been described by Pollock et al in the recent in-depth study of FCs managing medicines at home [12]. Our work expands on this in exploring how injectable medications and patients’ needs in the last days of life can increase this feeling of responsibility.…”
Section: Discussionmentioning
confidence: 71%
“…The considerable effort and burden of responsibility for medications, especially controlled drugs, has been described by Pollock et al in the recent in-depth study of FCs managing medicines at home [12]. Our work expands on this in exploring how injectable medications and patients’ needs in the last days of life can increase this feeling of responsibility.…”
Section: Discussionmentioning
confidence: 71%
“…There remains an underestimation of the support needed for patients and family caregivers to effectively self-manage care and COVID-19 has added to this burden. The managing medicines study ( Pollock et al , 2021 ) reinforced earlier findings that it is often the day-to-day practical problems associated with medicine use that lead to unintentional non-adherence. Concerns and anxiety can also arise around poor symptom control and administering potent medicines (e.g.…”
Section: The Shifting Care Landscape: Consequences For Patients and F...mentioning
confidence: 79%
“…This may include dedicated support for patients and families in managing complex medicines regimes and help in navigating a complex and sometimes bureaucratic system of care. A striking finding from the managing medicines study was the notable lack of patient, family caregiver and professional awareness and use of the community pharmacist's knowledge, skill sets and ability to provide advice and support for medicine-related issues or problems ( Pollock et al , 2021 ). Even established NHS funded medication review services that aim to improve patients' knowledge of medicines and use ( Latif et al.…”
Section: A Case For Greater Community Pharmacist Involvementmentioning
confidence: 99%
“…To use dosettes effectively, patients must have reasonable cognitive and organisational skills, memory recall, problem-solving abilities and dexterity. In a British report [ 22 ], the terminally ill patient required his medication to be decanted from the dosette by his wife due to difficulty handling the tablets with the dosette. In addition, dosettes replace the original medication packaging, meaning it can be difficult to obtain further information about the medication.…”
Section: Discussionmentioning
confidence: 99%
“…Although these methods provide relevant data about which packaging designs tend to fail in terms of accessibility to medication, they do not investigate the complexity experienced by people when handling a multitude of packaging and dosage methods in their own homes. One study has been identified describing the use of medications in the home setting, providing a case study of medication packaging format and user experiences for terminally ill patients [ 22 ]. Yet, little is known about the daily habits older people follow to take their medication and the implications of using multiple medication packaging to manage chronic diseases to a person’s life and general well-being.…”
Section: Introductionmentioning
confidence: 99%